Flexoelectricity in an oxadiazole bent-core nematic liquid crystal - PANOV, VITALI (My University, 2014)
We have determined experimentally the magnitude of the difference in the splay and bend flexoelectric coefficients, |e1 − e3|, of an oxadiazole bent-core liquid crystal by measuring the critical voltage for the formation of flexodomains together with their wave number. The coefficient |e1 − e3| is found to be a factor of 2–3 times higher than in most conventional calamitic nematic liquid crystals, varying from 8 pCm−1 to 20 pCm−1 across the ∼60 K—wide nematic regime. We have also calculated the individual flexoelectric coefficients e1 and e3, with the dipolar and quadrupolar contributions of the bent-core liquid crystal by combining density functional theory calculations with a molecular field approach and atomistic modelling. Interestingly, the magnitude of the bend flexoelectric coefficient is found to be rather small, in contrast to common expectations for bent-core molecules. The calculations are in excellent agreement with the experimental values, offering an insight into how molecular parameters contribute to the flexoelectric coefficients and illustrating a huge potential for the prediction of flexoelectric behaviour in bent-core liquid crystals.
Keywords: Density functional theory, Soft matter, Energy harvesting, Electrostatics, Nematic liquid crystals, Thermotropic liquid crystals, Dielectric materials, Elastic modulus, Optical computing, Chemical compounds